2021
DOI: 10.1002/pbc.28988
|View full text |Cite
|
Sign up to set email alerts
|

Short sleep duration and physical and psychological health outcomes among adult survivors of childhood cancer

Abstract: Background: To examine associations between phenotypes of short sleep duration and clinically assessed health conditions in long-term survivors of childhood cancer. Methods: Survivors recruited from the St. Jude Lifetime Cohort (n = 911; 52% female; mean age 34 years; 26 years postdiagnosis) completed behavioral health surveys and underwent comprehensive physical examinations. Sleep was assessed with the Pittsburgh Sleep Quality Index. Short sleep was defined as ≤6 h per night with phenotypes of short sleep in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…2,3 This substantial improvement in survival has resulted in a steadily growing population of childhood cancer survivors, who are, however, at increased risk of a wide range of somatic and psychiatric disorders, adverse mental late effects such as fatigue, neurocognitive sequelae (eg, impairments in memory), anxiety, depression, sleep disturbances and long-term socioeconomic consequences, such as lower educational attainment and unemployment. [4][5][6][7][8][9][10][11][12] These late effects may have a negative impact on the quality of life (QoL) of survivors. 13 For the sake of simplicity, the population of survivors who were diagnosed with cancer before the age of 21 will henceforth be referred to as childhood cancer survivors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 This substantial improvement in survival has resulted in a steadily growing population of childhood cancer survivors, who are, however, at increased risk of a wide range of somatic and psychiatric disorders, adverse mental late effects such as fatigue, neurocognitive sequelae (eg, impairments in memory), anxiety, depression, sleep disturbances and long-term socioeconomic consequences, such as lower educational attainment and unemployment. [4][5][6][7][8][9][10][11][12] These late effects may have a negative impact on the quality of life (QoL) of survivors. 13 For the sake of simplicity, the population of survivors who were diagnosed with cancer before the age of 21 will henceforth be referred to as childhood cancer survivors.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of more effective treatment, the 5‐year survival after childhood cancer has increased markedly over the past few decades and exceeds 80% in most European countries 2,3 . This substantial improvement in survival has resulted in a steadily growing population of childhood cancer survivors, who are, however, at increased risk of a wide range of somatic and psychiatric disorders, adverse mental late effects such as fatigue, neurocognitive sequelae (eg, impairments in memory), anxiety, depression, sleep disturbances and long‐term socioeconomic consequences, such as lower educational attainment and unemployment 4‐12 . These late effects may have a negative impact on the quality of life (QoL) of survivors 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, previous studies using both objective and self-reported methods did not show robust associations of SB with lower total body and lumbar spine aBMD z -score (12–14). Research in children and adolescents does not consistently show associations of sleep with aBMD parameters (15), but short sleep has been reported in almost half of 911 adult pediatric cancer survivors (16). The existing literature regarding the associations of physical activity, SB, and sleep with bone health in young pediatric cancer survivors is limited by important knowledge gaps including self-reported measures, small sample sizes, and methodological shortcomings.…”
mentioning
confidence: 99%